The American evangelical story: a history of the movement - Sweeney, Douglas A. (Baker Academic, 2005)
Evangelical : what's in a word? -- A surprising work of God : the eighteenth-century revival -- Crafting new wineskins : institutionalizing the movement -- As the waters cover the sea : the rise of evangelical missions -- Crossing the color line without working to erase it : evangelical history in black and white -- In search of a higher Christian life : the holiness, Pentecostal, and charismatic movements -- Standing on the promises through howling storms of doubt : fundamentalism and neoevangelicalism -- Conclusion : the future of evangelicalism